FAKTOR-FAKTOR YANG MEMPENGARUHI KETERLAMBATAN BICARA DAN BAHASA PADA ANAK BALITA: STUDI LITERATUR - Merita Meliyafara Pratiwi; Triatmi Andri Yanuarini; Erna Rahma Yani (STIKes Al-Insyirah Pekanbaru, 2022)
ABSTRACT Speech and language delays are developmental problems that can occur in toddlers. Speech and language delays can be influenced by several factors, both child factors, and parental factors. The purpose of this literature study is to obtain an overview of the factors that influence speech and language delays in children under five. This literature study research uses a systematic mapping study design with literature sources obtained from the Pubmed, Wiley, Science Direct, Proquest, SINTA, and Google Scholar databases. The literature collection strategy using PEOS was then selected to produce 27 articles that matched the research criteria using the 2017-2021 publication year. Based on the 27 in children under five, namely male gender, prenatal and perinatal history that affect premature birth and low birth weight, application of parenting patterns that can affect the application of parenting that less precise, the duration of the use of gadgets that affect that is more than 30 minutes/day, and the provision of stimulation that can affect the lack of accuracy in giving a stimulation. There is a relationship between sex factors, prenatal and perinatal history, application of parenting patterns, duration of gadget use, and stimulation with speech and language delays. The importance of monitoring during pregnancy, preparing to become prospective parents, and conducting early detection of growth and development after the child is born.